Long-service-life copper-titanium laminated metal etching solution and etching method
By adopting a formula with low hydrogen peroxide content and no inorganic acid in the copper-titanium laminated metal etching solution, combined with ether stabilizers, organic acid salts, complexing agents and other components, the glass substrate corrosion problems caused by the easy decomposition of hydrogen peroxide in the existing copper etching solution and the inorganic acid corrosion problem is solved, and a long-life, safe and efficient etching effect is achieved.
Patent Information
- Application Number
- CN202411738573.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
AI Technical Summary
The hydrogen peroxide content in existing copper etching liquid is too high and easy to decompose, the etching life is short, and the introduction of inorganic acid will accelerate the corrosion of the glass substrate and affect the performance of the structural sheet.
A copper-titanium laminated metal etching liquid with low hydrogen peroxide content is used, which does not contain inorganic acids. It uses ethers as hydrogen peroxide stabilizers, and combines organic acids, organic salts, complexing agents and metal corrosion inhibitors to form a stable etching liquid.
It achieves a long service life, reduces the decomposition speed of hydrogen peroxide, avoids corrosion of glass substrates caused by inorganic acids, and improves safety and uniformity of etching effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal etching, and in particular relates to a long-life copper-titanium laminated metal etching liquid and an etching method. Background Art
[0002] As one of the mainstream display device products, thin film transistor-liquid crystal display (TFT-LCD) has many advantages such as thin body and no radiation, so its application is gradually expanding. In recent years, the process technology of large-size panels has also been continuously innovated, which has led to the continuous expansion of the application of copper wire process in panel manufacturing. In the copper wire process, a series of process flows such as pre-treatment, gluing, exposure, development, etching, etc. are required to prepare the copper circuit with a specific structure required by the liquid crystal panel, and subsequent coating and other processes such as coating of other circuit layers are carried out.
[0003] Since copper is easy to diffuse, a laminated structure is generally designed on a substrate according to conditions such as impedance. Currently, two-layer substrates that are more commonly used have structures such as Cu / Ti and Cu / MoNb. For this type of etching process using laminated metal substrates of different thicknesses, a wet etching technique that is economical, effective and easy to operate is preferred. Wet etching technology can evenly etch the substrate, so that the metal film forms a specific pattern. In the existing copper etching liquid technology, most of them contain high fluorine ion concentrations, and some contain phosphorus elements. The waste liquid produced is very unfriendly to the environment, and the etching life is short, resulting in an increase in usage, and the efficient use of etching liquid cannot be achieved. As for the laminated metal etching liquids such as Cu / Ti and Cu / MoNb with thicker film layers, in order to achieve the etching effect, high-concentration hydrogen peroxide will be used, which has a high safety hazard.
[0004] Chinese patent CN113355673A discloses a copper and titanium laminated metal etching liquid, a preparation method and a real-time purification system. The two-agent copper and titanium laminated metal etching liquid proposed in the patent requires a main agent with a high hydrogen peroxide content and an auxiliary agent with a high fluorine ion concentration. During the use of the etching liquid, a certain amount of auxiliary agent needs to be added for each 500ppm increase in the metal ion concentration of the main agent to complete normal etching. The process is cumbersome and the etching life is short.
[0005] Chinese patent CN118516673A discloses an MTD-Cu-MTD etching solution and etching method, which uses a copper etching solution of a hydrogen peroxide system, can meet the etching requirements of MTD-Cu-MTD structures of different thicknesses for panels, achieve efficient use of the etching solution, and reduce etching costs. However, the life of the etching solution is not paid attention to, and experiments have found that its etching life is relatively short.
[0006] Chinese patent CN111647888A discloses a copper etching solution with a long etching life, which adds additives such as organic acid, secondary oxidant, chelating agent and pH regulator to hydrogen peroxide to slow down the decomposition of hydrogen peroxide, improve the stability of the etching solution, and extend the life of the etching solution.
[0007] However, the existing copper etching solutions all require the addition of inorganic acid and hydrogen peroxide to promote the oxidation reaction in a synergistic manner and reduce the effect of hydrogen peroxide decomposition on etching. However, the introduction of inorganic acid will accelerate the corrosion of the glass substrate, thereby affecting the performance of the structural piece. In addition, the etching life of the etching solution also has room for further improvement. Summary of the invention
[0008] In response to the above technical problems, the present invention provides a long-life copper-titanium laminated metal etching solution and etching method, which have good etching effect under low hydrogen peroxide content and without inorganic acid. As the copper ion concentration in the etching solution gradually increases, the etching morphology still has a stable etching cone angle and CD bias, and has a long service life.
[0009] In order to achieve the above-mentioned purpose, the present invention provides a long-life copper-titanium laminated metal etching solution, which is composed of the following raw materials in percentage by mass: 1-6% hydrogen peroxide, 5-9% organic acid, 3-7% organic salt, 1-3% hydrogen peroxide stabilizer, 0.5-0.9% fluoride ion source, 0.01-0.6% metal corrosion inhibitor, 1-5% complexing agent, and the balance is water.
[0010] Preferably, the organic acid is one or more of tartaric acid, citric acid, gluconic acid, succinic acid and oxalic acid.
[0011] Preferably, the organic salt is one or more of ammonium tartrate, ammonium citrate, and ammonium D-gluconate.
[0012] Preferably, the hydrogen peroxide stabilizer is one or more of propylene glycol butyl ether, propylene glycol methyl ether, diethylene glycol monobutyl ether, and diethylene glycol monomethyl ether.
[0013] Preferably, the fluoride ion source is one or more of fluoroboric acid, sodium fluoride, sodium bifluoride, and triethylamine trihydrofluoride.
[0014] Preferably, the metal corrosion inhibitor is an azole compound; the azole compound is a triazole compound and / or a tetrazole compound.
[0015] More preferably, the triazole compound is any one of 5-carboxybenzotriazole, methylbenzotriazole, 1H-1,2,3-triazole and 1,2,4-triazole; and the tetrazole compound is tetrazole or 5-(p-tolyl)-1H-tetrazole.
[0016] Further preferably, the triazole compound and the tetrazole compound are miscible in any ratio.
[0017] Preferably, the complexing agent is a water-soluble polymer and / or a water-soluble polysaccharide.
[0018] Further preferably, the complexing agent is composed of a water-soluble polymer and a water-soluble polysaccharide in a mass ratio of 1:2-1:4.
[0019] More preferably, the water-soluble polymer is polyaspartic acid or phosphonocarboxylic acid copolymer; the water-soluble polysaccharide is any one of fructan, mannan and dextran. The degree of polymerization of polyaspartic acid is 5-9, and the purity of phosphonocarboxylic acid copolymer is ≥30%.
[0020] Further preferably, the usage ratio of the metal corrosion inhibitor to the complexing agent is 1:11-1:100.
[0021] The present invention also provides a copper-titanium laminate etching method, wherein a structure sheet containing the copper-titanium laminate is immersed in the copper-titanium laminate metal etching solution, and is etched at 30-40° C. for 1-5 minutes, and then taken out and cleaned to complete the etching.
[0022] Preferably, in the structure sheet containing the copper-titanium laminate, the thickness of copper is 1000-6000Å, and the thickness of titanium is 50-500Å.
[0023] The beneficial effects of the present invention are: 1. The metal etching solution is prepared with a lower content of hydrogen peroxide, which overcomes the problem of high hydrogen peroxide content and easy decomposition in conventional metal etching solutions, thereby improving safety. In addition, ethers are used as hydrogen peroxide stabilizers to reduce the decomposition rate of hydrogen peroxide, further extending the service life of the metal etching solution.
[0024] 2. Without using inorganic acid, the prepared metal etching solution can still obtain a good etching morphology without titanium tailing when etching a structure sheet containing a copper-titanium stack, has little corrosion to the underlying glass substrate, is economical and environmentally friendly, further improves safety and reduces etching costs.
[0025] 3. Water-soluble polysaccharides and water-soluble polymers containing multiple functional groups such as hydroxyl, amino, carboxyl or organic phosphine ligands can be used as chelating agents to effectively chelate copper ions and form stable complexes. The synergistic effect of quantitative azole metal corrosion inhibitors and chelating agents ensures that even in the case of low hydrogen peroxide content, as the copper ion concentration gradually increases, the etching morphology still has a stable etching cone angle and CD bias. Organic acids / organic salts such as tartaric acid and sodium tartrate contain multiple functional groups such as carboxyl groups. They can be used as chelating agents to extend the life of the etching solution, and can also be used as a buffer system to improve the uniformity of the etching effect of the solution.
[0026] 4. The present invention prepares a copper-titanium laminated metal etching solution with a long life, high stability and uniform etching effect, and is also suitable for etching other copper alloys and multi-layer metal film layers. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further explained below in conjunction with specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be construed as limiting the present invention. The protection scope of the present invention shall be subject to the contents recorded in the claims. Any modification or replacement made by a person skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.
[0028] Example 1 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.06% metal corrosion inhibitor, 2.0% polyaspartic acid, and the balance is deionized water; wherein the metal corrosion inhibitor is composed of 5-carboxybenzotriazole and tetrazole in a mass ratio of 1:2.
[0029] Preparation method: Add various raw materials into deionized water and stir evenly to obtain copper-titanium laminated metal etching solution.
[0030] Example 2 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.06% metal corrosion inhibitor, 1.0% polyaspartic acid, and the balance is deionized water; wherein the metal corrosion inhibitor is composed of methylbenzotriazole and tetrazole in a mass ratio of 2:1.
[0031] Example 3 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.09% metal corrosion inhibitor, 1.0% polyaspartic acid, and the balance is deionized water; wherein the metal corrosion inhibitor is composed of 5-carboxybenzotriazole and tetrazole in a mass ratio of 7:2.
[0032] Example 4 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.06% metal corrosion inhibitor, 2.0% polyaspartic acid, and the balance is deionized water; wherein the metal corrosion inhibitor is composed of 5-carboxybenzotriazole and 5-(p-tolyl)-1H-tetrazole in a mass ratio of 2:1.
[0033] Example 5 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.1% tetrazole, 1.5% complexing agent, and the balance is deionized water; wherein the complexing agent is composed of a phosphonocarboxylic acid copolymer and fructan in a mass ratio of 1:2.
[0034] Example 6 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 1% hydrogen peroxide, 5% citric acid, 3% ammonium citrate, 1% diethylene glycol monobutyl ether, 0.5% sodium fluoride, 0.01% 1,2,4-triazole, 1% dextran, and the balance is deionized water.
[0035] Example 7 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 6% hydrogen peroxide, 9% gluconic acid, 7% ammonium D-gluconate, 3% propylene glycol methyl ether, 0.9% triethylamine trihydrofluoride, 0.6% 1H-1,2,3-triazole, 5% polyaspartic acid, and the balance is deionized water.
[0036] Comparative Example 1 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, and the balance is deionized water.
[0037] Comparative Example 2 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.04% 5-carboxybenzotriazole, and the balance is deionized water.
[0038] Comparative Example 3 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.05% 5-carboxybenzotriazole, 0.5% polyaspartic acid, and the balance is deionized water.
[0039] Comparative Example 4 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.1% metal corrosion inhibitor, 5.5% complexing agent, and the balance is deionized water; wherein the metal corrosion inhibitor is composed of 5-carboxybenzotriazole and tetrazole in a mass ratio of 1:1; and the complexing agent is composed of a phosphonocarboxylic acid copolymer and fructan in a mass ratio of 1:1.
[0040] Comparative Example 5 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.7% metal corrosion inhibitor, 1.5% complexing agent, and the balance is deionized water; wherein the metal corrosion inhibitor is composed of 5-carboxybenzotriazole and tetrazole in a mass ratio of 2:1; and the complexing agent is composed of a phosphonocarboxylic acid copolymer and polyaspartic acid in a mass ratio of 1:2.
[0041] Comparative Example 6 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 7.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.03% metal corrosion inhibitor, 1.5% complexing agent, and the balance is deionized water; wherein the metal corrosion inhibitor is composed of 5-carboxybenzotriazole and tetrazole in a mass ratio of 2:1; and the complexing agent is composed of polyaspartic acid and fructan in a mass ratio of 2:1.
[0042] Comparative Example 7 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 7.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.10% tetrazole, 1.5% iminodiacetic acid, and the balance is deionized water.
[0043] Comparative Example 8 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 4.5% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.10% tetrazole, 1.5% iminodiacetic acid, and the balance is deionized water.
[0044] Comparative Example 9 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 3.0% hydrogen peroxide, 10.0% tartaric acid, 6.1% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.7% fluoroboric acid, 0.10% tetrazole, 1.5% fructan, and the balance is deionized water.
[0045] Comparative Example 10 A copper-titanium laminated metal etching solution is composed of the following raw materials in percentage by mass: 7.0% hydrogen peroxide, 5.0% tartaric acid, 5.0% ammonium tartrate, 2.0% propylene glycol butyl ether, 0.03% tetrazole, 2.0% iminodiacetic acid, 0.5% phosphoric acid, and the balance is deionized water.
[0046] Result detection: Take the copper-titanium laminated metal etching solution prepared in the above examples and comparative examples, heat it to 35°C, and immerse the copper-titanium laminated structure sheet in the etching solution by splitting, stirring at a speed of 300 rpm / min, record the time required for the structure sheet to just become transparent during the etching process, that is, the etching endpoint time (EPD), and then adjust the OE time to etch out the side etching amount (CD bias, which refers to the distance between the end of the photoresist and the end of the metal layer, and the distance is preferably 0.6-0.8 μm on one side) that can meet customer needs. The etching cone angle is the angle from the bottom edge of the metal to the lower edge of the photoresist protection, preferably 30°-50°. After the etched structure sheet is split, the cross section is observed by SEM to measure the etching cone angle and CD bias.
[0047] Add a certain amount of copper powder (6000ppm) to the etching solution, dissolve it, and then etch it at the same temperature and for the same time. Observe whether the etching morphology is consistent with that without adding copper powder (0ppm). Determine the etching life of the etching solution at once. The results are shown in the following table:
[0048] The results show that: at low hydrogen peroxide and lower fluorine content, there is a buffering effect of organic acids / organic salts such as tartaric acid and ammonium tartrate. At 0ppm, the etching solution has a smooth etching cone angle and no titanium tailing.
[0049] When there is no metal corrosion inhibitor and chelating agent in the etching solution (Comparative Example 1), the etching solution life is less than 6000ppm, and as the amount of copper powder gradually increases, the etching cone angle and CD bias gradually increase; when there is a single metal corrosion inhibitor and no chelating agent in the etching solution (Comparative Example 2), as the amount of copper powder gradually increases, the single metal corrosion inhibitor cannot dynamically adjust the etching cone angle, and a two-stage angle gradually appears, and the absence of a chelating agent makes the CD bias unstable.
[0050] When polyaspartic acid is used as a complexing agent (Example 1), the etching solution contains two appropriate amounts of azole metal corrosion inhibitors, the etching morphology has an etching cone angle of appropriate size, and the angle and CD bias are stable when the life reaches 6000ppm, while in Comparative Example 4, only one azole is contained, and the angle and CD bias become larger and have a two-stage angle when the life reaches 6000ppm; when phosphonocarboxylic acid copolymer and fructan are used as complexing agents (Example 5), the etching solution contains a tetrazole metal corrosion inhibitor to have a stable long etching life, and in Comparative Example 5, the two corrosion inhibitors interact with each other, so that when the copper powder content in the etching solution reaches a higher content, the etching morphology shows an obvious two-stage angle; when polyaspartic acid and fructan / phosphonocarboxylic acid copolymer are used as complexing agents, due to the strong complexation, the etching morphology shows an obvious two-stage angle and the CD bias becomes smaller when the life reaches 6000ppm.
Claims
1. A long-life copper-titanium laminated metal etching solution, characterized in that: The invention is composed of the following raw materials in percentage by mass: 1-6% hydrogen peroxide, 5-9% organic acid, 3-7% organic salt, 1-3% hydrogen peroxide stabilizer, 0.5-0.9% fluoride ion source, 0.01-0.6% metal corrosion inhibitor, 1-5% complexing agent, and the balance is water.
2. A long-life copper-titanium laminated metal etching solution according to claim 1, characterized in that: The organic acid is one or more of tartaric acid, citric acid, gluconic acid, succinic acid and oxalic acid.
3. The long-life copper-titanium laminated metal etching solution according to claim 1, characterized in that: The organic salt is one or more of ammonium tartrate, ammonium citrate and D-ammonium gluconate.
4. The long-life copper-titanium laminated metal etching solution according to claim 1, characterized in that: The hydrogen peroxide stabilizer is one or more of propylene glycol butyl ether, propylene glycol methyl ether, diethylene glycol monobutyl ether, and diethylene glycol monomethyl ether.
5. The long-life copper-titanium laminated metal etching solution according to claim 1, characterized in that: The fluoride ion source is one or more of fluoroboric acid, sodium fluoride, sodium hydrogen fluoride, and triethylamine trihydrofluoride.
6. The long-life copper-titanium laminated metal etching solution according to claim 1, characterized in that: The metal corrosion inhibitor is an azole compound; the azole compound is a triazole compound and / or a tetrazole compound; the triazole compound is any one of 5-carboxybenzotriazole, methylbenzotriazole, 1H-1,2,3-triazole and 1,2,4-triazole; the tetrazole compound is tetrazole or 5-(p-tolyl)-1H-tetrazole.
7. The long-life copper-titanium laminated metal etching solution according to claim 1, characterized in that: The complexing agent is a water-soluble polymer and / or a water-soluble polysaccharide.
8. The long-life copper-titanium laminated metal etching solution according to claim 7, characterized in that: The complexing agent is composed of a water-soluble polymer and a water-soluble polysaccharide in a mass ratio of 1:2-1:
4.
9. A long-life copper-titanium laminated metal etching solution according to claim 8, characterized in that: The water-soluble polymer is polyaspartic acid or phosphonocarboxylic acid copolymer; the water-soluble polysaccharide is any one of fructan, mannan and dextran.
10. A method for etching a copper-titanium laminate, characterized in that: The structure sheet containing the copper-titanium laminate is immersed in the copper-titanium laminate metal etching solution according to any one of claims 1 to 8 for etching.
Citation Information
Patent Citations
Copper etching solution with long etching life
CN111647888A
Copper and titanium laminated metal etching solution, and preparation method and real-time purification system thereof
CN113355673A
MTD-Cu-MTD etching solution and etching method
CN118516673A